1970
DOI: 10.1111/j.1365-2621.1970.tb12165.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aging on Palatability and Selected Related Characteristics of Pork Loin

Abstract: SUMMARY Selected characteristics of 24 left pork loins representing 4 aging (chilling at 36°F) periods (1, 4, 8 and 12 days) were investigated. The loin was cut into 4 sections: al the 4th to 8th thoracic vertebra, b) the 8th to 12th thoracic vertebra. c) the 12th thoracic to the 1st lumbar vertebra and dl the 1st to 5th lumbar vertebra. 2, 1.5‐in. chops were cut from the posterior end of each section and used for measurements on the cooked meat (cooking time and losses, palatability scores, shear value, water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

1980
1980
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 5 publications
2
5
0
Order By: Relevance
“…The moisture percentage of the semimembranosus and biceps femoris were not affected by backfat thickness. When averaged over backfat level, moisture percentage of the longissimus muscle and psoas major are in good agreement with reported literature (Judge et al 1960;Harrison et al 1970;Shuler et al 1970;Deethardt and Tuma 1971;Lee et al 1971;Henning et al 1973;Skelley et al 1973;Bakke and Standal 1975;Lawrie et al 1985). Moisture percentages reported in this study for the three major ham muscles were slightly lower than values found by Lin et al (1985).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The moisture percentage of the semimembranosus and biceps femoris were not affected by backfat thickness. When averaged over backfat level, moisture percentage of the longissimus muscle and psoas major are in good agreement with reported literature (Judge et al 1960;Harrison et al 1970;Shuler et al 1970;Deethardt and Tuma 1971;Lee et al 1971;Henning et al 1973;Skelley et al 1973;Bakke and Standal 1975;Lawrie et al 1985). Moisture percentages reported in this study for the three major ham muscles were slightly lower than values found by Lin et al (1985).…”
Section: Resultssupporting
confidence: 91%
“…When averaged over backfat, the raw intramuscular crude fat percentage of the longissimus muscle was 4.3%. Other research has indicated raw intramuscular fat percentage of the longissirnus muscle to range from 1.23 to 5.18% in studies evaluating slaughter weight (Emerson et al 1964), carcass quality (Judge et al 1960;Skelley et al 1973), aging periods (Harrison et al 1970) and rate of gain and backfat thickness (Bakke and Standal 1975). The low intramuscular crude fat percentage (2.5% averaged over backfat) of the psoas major is in good agreement with values from the literature (Lawrie et al 1963;Allen et al 1967).…”
Section: Resultssupporting
confidence: 79%
“…Thus, consistent results have not been obtained, although there have been many studies regarding the improvement of beef fiavor during postmortem aging. With regard to pork, Harrison et al ( 1970) have observed that the aging of pork at 2'C for 1, 4, 8 and 12 days does not improve its flavor. Bennett et al ( 1973) also showed that the storage of pork loin from 2 to 6 days after slaughter at 2'C has no infiuence on its fiavor.…”
Section: Improvement Of Meat Tastementioning
confidence: 99%
“…Postmortem aging of meat has been reported to improve tenderness (Dransfield and modes 1975;Harrison et al 1970;Herring et al 1966;Joseph 1976), flavor (Jennings er al. 1976;Sink and Smith 1972) and overall palatability (Jennings er al.…”
Section: Introductionmentioning
confidence: 99%